The Plasmodium PI(4)K inhibitor KDU691 selectively inhibits dihydroartemisinin-pretreated Plasmodium falciparum ring-stage parasites - Dembele, L; Ang, X; Chavchich, M; Bonamy, GMC; Selva, JJ; Lim, MY; Bodenreider, C; Yeung, BKS; Nosten, F; Russell, BM; Edstein, MD; Straimer, J; et al. (Springer Nature, 2017)
Malaria control and elimination are threatened by the emergence and spread of resistance to artemisinin-based combination therapies (ACTs). Experimental evidence suggests that when an artemisinin (ART)-sensitive (K13 wild-type) Plasmodium falciparum strain is exposed to ART derivatives such as dihydroartemisinin (DHA), a small population of the early ring-stage parasites can survive drug treatment by entering cell cycle arrest or dormancy. After drug removal, these parasites can resume growth. Dormancy has been hypothesized to be an adaptive physiological mechanism that has been linked to recrudescence of parasites after monotherapy with ART and, possibly contributes to ART resistance. Here, we evaluate the in vitro drug sensitivity profile of normally-developing P. falciparum ring stages and DHA-pretreated dormant rings (DP-rings) using a panel of antimalarial drugs, including the Plasmodium phosphatidylinositol-4-OH kinase (PI4K)-specific inhibitor KDU691. We report that while KDU691 shows no activity against rings, it is highly inhibitory against DP-rings; a drug effect opposite to that of ART. Moreover, we provide evidence that KDU691 also kills DP-rings of P. falciparum ART-resistant strains expressing mutant K13.